The role of private standards for manufactured food exports from developing countries - Malte Ehrich; Axel Mangelsdorf (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2016)
The effect of food standards on agricultural trade flows remains unclear. We contribute to the debate with a unique dataset that contains the number of food processing firms of 88 countries from 2008 to 2013 that are certified with the International Featured Standard (IFS). Based on a theoretical framework that combines Melitz-type firm heterogeneity with quality upgrading, we estimate a gravity-model using the one-year lag of IFS as well as modern grocery distribution as an instrument to address potential endogeneity. We find that IFS increases c.p. bilateral exports on average of seven agricultural product categories in both specifications. However, the effect remains only for upper- and middle-income countries once we separate by income and turns even negative for low income countries in the IV-specification. Hence, whereas IFS increases exports on average, it has a trade-impeding effect for low-income countries. Therefore, private standards are not a sufficient development policy tool to integrate low-income countries to the world trading system without being accompanied by other measures.
Keywords: F14; F18; F19; 330; agricultural trade; private food standards; manufactured food; gravity model